2000
DOI: 10.1242/dev.127.22.4891
|View full text |Cite
|
Sign up to set email alerts
|

The adhesion signaling molecule p190 RhoGAP is required for morphogenetic processes in neural development

Abstract: Rho GTPases direct actin rearrangements in response to a variety of extracellular signals. P190 RhoGAP (GTPase activating protein) is a potent Rho regulator that mediates integrin-dependent adhesion signaling in cultured cells. We have determined that p190 RhoGAP is specifically expressed at high levels throughout the developing nervous system. Mice lacking functional p190 RhoGAP exhibit several defects in neural development that are reminiscent of those described in mice lacking certain mediators of neural ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…A variety of cellular proteins contain polybasic regions embedded with serines and threonines, and phosphorylation of these amino acids, typically by PKC, has been found to reduce the electrostatic attraction of these regions for phospholipid membranes . We have previously demonstrated that p190A is phosphorylated by PKC both in vitro and in vivo in epithelial cells . Subsequently, we found that the PKC isoform α was the most efficient among the various PKC enzyme isoforms for phosphorylating both p190A and p190B proteins.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…A variety of cellular proteins contain polybasic regions embedded with serines and threonines, and phosphorylation of these amino acids, typically by PKC, has been found to reduce the electrostatic attraction of these regions for phospholipid membranes . We have previously demonstrated that p190A is phosphorylated by PKC both in vitro and in vivo in epithelial cells . Subsequently, we found that the PKC isoform α was the most efficient among the various PKC enzyme isoforms for phosphorylating both p190A and p190B proteins.…”
Section: Resultsmentioning
confidence: 93%
“…Antagonism of Rac and Rho activity has been demonstrated to be required for several vital biological functions such as neurite outgrowth or directed cell migration. p190GAPs seem to play a significant role in this process . Recent findings demonstrated that activated Rac1 was able to recruit p190B to the plasma membrane and enhance its RhoGAP activity, and this cross-talk between Rac and Rho GTPases was required for control of cell shape by integrin signaling .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, although defects in both CE and AC result in NTDs, failure of CE is correlated with spinal NTDs whereas failure of AC is correlated with anterior NTDs ( Greene et al, 1998 ; Hildebrand and Soriano, 1999 ; Brouns et al, 2000 ; Wallingford et al, 2002 ; Haigo et al, 2003 ), suggesting that although these two morphogenetic processes are both indispensable for NTC they have discrete spatial and temporal contribution during neural tube morphogenesis. However, at present the precise spatiotemporal contribution of these processes towards NTC is not clear.…”
Section: Introductionmentioning
confidence: 99%